Exclusivism, Inclusivism, and Pluralism in Islam: An Epistemological Analysis and Its Relevance to Religious Moderation in the Digital Age - Moh. Imron (Institut Agama Islam An-Nawawi Purworejo, 2026)
Religious pluralism in modern multicultural societies raises epistemological debates regarding exclusivism, inclusivism, and pluralism in Islam. Previous studies have tended to address religious pluralism in normative and descriptive terms, and thus have not yet comprehensively examined the epistemological contradictions between these paradigms in the context of the digital age. This study aims to analyze the epistemological differences among these three paradigms and formulate a model of religious practice relevant to contemporary society. The research employs a qualitative approach based on a literature review using the Systematic Literature Review (SLR) method and thematic analysis of various academic sources related to religious pluralism, Islamic education, and religious moderation. The results indicate that exclusivism is oriented toward truth absolutism, pluralism tends toward religious relativism, while the inclusive-contextual paradigm emerges as the most adaptive approach because it can proportionally integrate doctrinal commitment, social tolerance, humanistic dialogue, and digital moderation. This study offers an inclusive-contextual model as a synthesis between exclusive absolutism and pluralistic relativism in addressing the challenges of a multicultural society and digital disruption. These findings contribute to the development of Islamic education, digital da’wah, and the strengthening of religious moderation in contemporary Indonesia.